Autogenous hard palate mucosa: the ideal lower eyelid spacer?. Issue 10 (1st October 2001) - Wearne, Michael J; Sandy, Charles; Rose, Geoffrey E; Pitts, J; Collin, J R O
Abstract : BACKGROUND/AIMS: Raising a displaced lower eyelid frequently involves recession of the lower eyelid retractors with interposition of a "spacer, " and several materials for this purpose have been described. This study reviewed the results of autogenous palatal mucosa in the treatment of lower eyelid displacement, including assessment of any donor site morbidity. METHODS: A retrospective case note review of consecutive patients treated at Moorfields Eye Hospital between 1993 and 1998. All patients underwent insertion of hard palate mucosa between the inferior border of the tarsus and the recessed conjunctiva and lower eyelid retractors. Parameters studied included the underlying diagnosis, measurements of lower lid displacement or retraction, related previous surgery, the experience of the operating surgeon, intraoperative and postoperative complications, surgical outcome, and length of follow up. The main outcome measure was the position of the lower eyelid relative to the globe in primary position of gaze. RESULTS: 102 lower eyelids of 68 patients were included and a satisfactory lid position was achieved in 87/102 (85%), with inadequate lengthening or significant recurrence of displacement occurring in 15 cases. Donor site haemorrhage requiring treatment in the early postoperative period occurred in seven patients (10%). CONCLUSION: Autogenous hard palate mucosa is an effective eyelid spacer and provides good long term support for the lower eyelid. Donor site complications are the main disadvantage, but may be minimised by attention to meticulous surgical technique and appropriate postoperative management.